2012
DOI: 10.4103/0976-237x.103623
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of mouth washes and herbal products against dental biofilm-forming bacteria

Abstract: Aim:To evaluate in vitro, the antimicrobial effect of Cymbopogon citrates (lemon grass), Plectranthusamboinicus (Mexican mint) and Conyzabonariensis (hairy fleabane) tinctures as well as pure and diluted commercial mouth washes (Malvatricin®, Periogard® and Listerine®) on wild isolates of Streptococcusmutans and reference strains of S. mutans, Streptococcus salivarius, Streptococcus oralis and Lactobacillus casei by determination of minimum inhibitory dilution (MID).Materials and Methods:0.12% chlorhexidine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…However, the effect on yeasts observed in this study can be considered moderate [25], since MIC was 125 µg / mL, being between 100 and 500 µg / mL, whereas the antibacterial effect was weak, with MIC of 1mg / mL. A previous study using dye formulation with C. citratus found no antibacterial effect [26].…”
Section: Discussioncontrasting
confidence: 55%
“…However, the effect on yeasts observed in this study can be considered moderate [25], since MIC was 125 µg / mL, being between 100 and 500 µg / mL, whereas the antibacterial effect was weak, with MIC of 1mg / mL. A previous study using dye formulation with C. citratus found no antibacterial effect [26].…”
Section: Discussioncontrasting
confidence: 55%
“…Antimicrobial effects of PO are commonly examined by agar disc/well diffusion assay and by measuring the zone of inhibition. Two such studies did not report the antimicrobial activity of PO and Mexican mint on S. mutans ATCC 25175 [ 7 , 9 ]. Conversely, another study found that high concentrations (1000–8000 ppm) of PO had antimicrobial activity and that 17-h S. mutans batch biofilm that formed on the walls of polystyrene tubes was inhibited by PO [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The malvatricin, in this study, had better result against E. faecalis, C. albicans and S. aureus compared to chlorhexidine, saline, anesthesic and propolis. Others researches have demonstrated effectiveness of the mouthwash against S.mutans, S. salivarius, S.oralis and L. casei [11,25]. The malvatricin is presented as promising substance to be evaluated as a vehicle in association with calcium hydroxide in the endodontic treatment, however there are no studies about the use of malvatricin in endodontics.…”
Section: Discussionmentioning
confidence: 99%